Analyse du risque inondation de l’agglomération de Tindouf : une approche pour le développement durable - Smahi Zakaria; Zeroual Ibrahim; Hami Khelifa (Études Caribéennes)
The city of Tindouf is characterized by the frequency of flood zones which dangerously affect many densely populated neighbourhoods. These sites affected by major floods during thunderstorms and display great vulnerability for a population of 75,000 inhabitants, but also no less than 15,000 constructions threatened with ruins: by the extent of the spectacular damage to constructions. The city of Tindouf offers all the conditions of high potential for habitat degradation in Algeria. Floods originate from meteorological and/or hydrological events of a stochastic nature are very difficult to predict as to their return period and their intensity. A methodological approach on the old agglomerations grouping the districts [Remadine - Moussani - Guessabi] thus making it possible to delimit the vulnerable zones and to propose urban developments for their protections. The results obtained show the spatial distribution of the vulnerability of historic districts and propose a conservation approach for sustainable development.